A experiência pedagógica de uma escritura dionisíaca - Muniz, Cellina Rodrigues (2009)
The present study analyses determined practices of writing from a group of individuals who lived im Benfica district in the city of Fortaleza, Ceará, Brazil, in early of the years 2000. From their living together, they wrote, edited and distributed the fanzines PalavraDesordem (in a series of eleven editions) and Sarrabuio de Tertúlia (in three editions), besides on edition of the alternative magazine Pindaíba. Having the support of thoughts from authors such as Nietzsche, Maffesoli, Foucault, Maingueneau and Larrosa, this study postulates that the practices implied in the writing of this discoursive community, observed in the scenary of post-modernity, may be interpreted as a pedagogical experience that re-modernize the myth of Dionyso, giving value to erroneous principles and plurality in the contemporary societies. The fanzines and the alternative magazine produced by the group bring approaches from the point of some principles and procedures of the Discourse Analysis, as they also used for analysis written and/or oral declarations given by the individuals themselves in semi-structured interviews. The analyses comes from categories, for instance, genetc rites, discursive positions and self forms associated to the writing in question, in its cration, circulation and makes evident how the manifestation of Dionysian is done: the loafing, indiscipline, cult to live in group, praise to drunkenness, the appeal to laughter, the cruelty on sight, the erroneous (in the functions of authorship, in the self care and in the concepts to writing) and the creation (in the ways of doing and assuming knowledge). The thesis conclude that those individuals being author of such writing makes them individuals of the experience, that can be expressed as a pedagogy of life.